2022
DOI: 10.3390/ijerph191711107
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D Knowledge, Behavior and Attitude with BMI Status among Arab Adults

Abstract: This study aims to investigate the association of vitamin D (VD) knowledge, behavior, and attitude with BMI status among Saudi adults. This cross-sectional online survey included a total of 774 participants (M/F: 239/535). Knowledge about the overall sources of VD was highest in OB participants in correctly identifying sunlight (95.1%; p < 0.001) while significantly more OW participants answered food (83.1%; p = 0.04) and fortified food (66.5%; p = 0.02). However, 18.9% of OB participants also wrongly ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Moreover, 30.7% of them taking medications such as corticosteroid, antiepileptic, anticoagulant, weight loss, and anti-cholesterol drugs. This result was consistent with research done by Al-Daghri et al (2022) on VD status among Arab adults which reported that the most prevalent diseases among them were 9.3% DM, 9.2% HTN, 3.2% heart disease, 5.8% with dyslipidemia, 3.4% osteoporosis, 6.2% with arthritis, and 2.3% with bone fracture history. Also according to several studies, there is an association between such diseases, the medication, and the development of VDD (Aziz, & Azeez, 2020;Sohl et al, 2012;Wakeman, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, 30.7% of them taking medications such as corticosteroid, antiepileptic, anticoagulant, weight loss, and anti-cholesterol drugs. This result was consistent with research done by Al-Daghri et al (2022) on VD status among Arab adults which reported that the most prevalent diseases among them were 9.3% DM, 9.2% HTN, 3.2% heart disease, 5.8% with dyslipidemia, 3.4% osteoporosis, 6.2% with arthritis, and 2.3% with bone fracture history. Also according to several studies, there is an association between such diseases, the medication, and the development of VDD (Aziz, & Azeez, 2020;Sohl et al, 2012;Wakeman, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies from different parts of Saudi Arabia have assessed awareness and knowledge about VD in relation to various lifestyle behaviors and risk factors among adult males and females [ 24 , 25 , 26 , 27 ]. However, none of these studies focused on whether VD awareness and knowledge could reflect an attitude towards PA, or provided any information in this context.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 There is much evidence to show that there is insufficient knowledge about dietary sources of VD and negative attitudes towards sun exposure. 23,24 Recently, Al-Daghri and Alfawaz 25 reported inconsistent knowledge mainly about suitable sources of VD.…”
Section: Introductionmentioning
confidence: 99%